Data fusion of terrestrial laser scanner and remotely piloted aircraft systems points clouds for monitoring the coastal protection systems - Saponaro, M.; Pratola, L.; Capolupo, A.; Saponieri, A.; Damiani, L.; Fratino, U.; Tarantino, E. (Aquatic ecosystem health & management, 2020)
Frequently exposed to natural agents such as waves, wind, tides, storm activity, seasonal changes and anthropogenic agents, coastal areas are tangibly high energy environments and therefore subject to considerable dynamics. In order to mitigate and reduce the impacts on these areas, different types of coastal protection systems can be implemented. Rockwalls and breakwaters are the most ordinary structures and even if used precisely for coastal protection, these flexible structures can in turn be damaged or ineffective over time. Therefore, like the monitoring of coastal areas in terms of execution frequency and accuracy, the measurement of changes over time of these structures, in particular after significant events, can allow to carry out an economic maintenance service before a serious occurrence and costly damage. However, given the rapid evolution of the preservation state of coastal areas and protection structures, it is therefore essential to plan an equally frequent, practical and accurate structural-coastal monitoring. On the other hand, their accessibility can sometimes be dangerous or uncomfortable such as to compromise operations in the field. In this work, the application of two close-range detection techniques competitor, i.e. from the Terrestrial Laser Scanner and from Remote Piloted Aircraft Systems, aimed at the generation of three-dimensional reconstructions of a protection structure, was analyzed. By performing a cloud-to-cloud comparison, interesting considerations have been obtained on the precision that can be achieved and on the technical limits deriving from the two methodologies. Considering the economy and practicality of use, if used correctly, a Remote Piloted Aircraft Systems supported by a suitable geo-referencing and an optimized data processing, can produce accurate and coherent 3D reconstructions as those derivable from the Terrestrial Laser Scanner. Finally, the results obtained by merging the point clouds generated from the two different techniques were evaluated in order to identify any advantages in the structural maintenance of the systems.